2023
DOI: 10.3390/ijerph20064858
|View full text |Cite
|
Sign up to set email alerts
|

Sexually Transmitted Diseases among Saudi Women: Knowledge and Misconceptions

Abstract: The rate of sexually transmitted diseases is increasing globally. Thus, this study aimed to examine the Al akami female community’s knowledge about the nature of sexually transmitted diseases and their associated factors. The STDs-Knowledge Questionnaire (STDs-KQ) was utilized to collect data from the female community (355) in Jeddah, Saudi Arabia. The data were analyzed using JMP Statistics for Windows, version 15. The significance level was set at 0.05. The study reported that participants had a relatively l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 37 publications
(45 reference statements)
0
3
0
Order By: Relevance
“…In this study, participants who had no STIs in the last 12 months were likely not to have ever been tested for HIV. Studies have shown that understanding STIs in terms of acquisition, protection, prevention, and clinical signs and symptoms are limited among young people 68. Poor knowledge about STI screening and services could be one possible explanation for young women not knowing their STI statuses in this study.…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…In this study, participants who had no STIs in the last 12 months were likely not to have ever been tested for HIV. Studies have shown that understanding STIs in terms of acquisition, protection, prevention, and clinical signs and symptoms are limited among young people 68. Poor knowledge about STI screening and services could be one possible explanation for young women not knowing their STI statuses in this study.…”
Section: Discussionmentioning
confidence: 77%
“…Studies have shown that understanding STIs in terms of acquisition, protection, prevention, and clinical signs and symptoms are limited among young people. 68 Poor knowledge about STI screening and services could be one possible explanation for young women not knowing their STI statuses in this study. Lack of STI information and screening services, acceptability of services, fear of positive test results, fear of invasive procedures, self-consciousness of genital examination, anticipated stigma and confidentiality concerns have been found to impede STI screening uptake among young people.…”
Section: Discussionmentioning
confidence: 77%
“…Studies have shown that understanding of STIs in terms of acquisition, protection, prevention, and clinical signs and symptoms is low among young people. 61 Also, a lack of knowledge about STI screening and services could be one possible explanation for young women not knowing their STI statuses. There is growing evidence that lack of STI information and screening services, acceptability of services, fear of positive test results, fear of invasive procedures, the self-consciousness of genital examination, anticipated stigma, and confidentiality concerns are barriers to STI screening among young people.…”
Section: Discussionmentioning
confidence: 99%